Failure of Tooth Eruption: A Systematic Review and Meta-Analysis Integrating Genetic Etiology, Diagnostic Accuracy, and Clinical Management Outcomes - Maen Mahfouz; Eman Alzaben (2026)
ABSTRACT Background Failure of tooth eruption (FTE) encompasses mechanical impaction, primary failure of eruption (PFE), and syndromic disturbances. Since the seminal review by Suri et al. (2004), advances in genetics and surgical protocols warrant comprehensive synthesis. Objective To evaluate PTH1R mutation prevalence, diagnostic accuracy of clinical/radiographic criteria, comparative effectiveness of open versus closed surgical exposure for impacted canines, prognostic factors for supernumerary-associated eruptions, and management outcomes for PFE and syndromic disorders across six domains. Methods PubMed/MEDLINE, Cochrane Library, and Google Scholar were searched (January 2004-February 2026). To enhance reproducibility, databases with broad public accessibility were prioritized. Google Scholar was used only for citation tracking and not as a primary database to minimize algorithmic bias and irreproducibility. PRISMA 2020 guidelines were followed. Protocol registered on OSF (DOI: 10.17605/OSF.IO/R5X76). Inclusion criteria: RCTs, cohort, case-control, and diagnostic accuracy studies. Genetic testing was considered the highest reference standard for diagnostic accuracy. Risk of bias assessed using ROBINS-I, QUADAS-2, and RoB 2.0. Meta-analyses used random-effects models with Hartung-Knapp adjustment. Heterogeneity was assessed using I² statistics, with sources explored through subgroup analyses, meta-regression, and prognostic factor analysis. GRADE evaluated evidence quality. Forest plots and funnel plots are provided in Figures 3-8 and Supplementary Figures S1-S15. Results From 3,587 records, 94 studies (9,156 patients) were included across six domains. Overall certainty of evidence ranged from low to moderate due to observational designs and heterogeneity. Domain 1 (Genetic Basis): PTH1R mutation prevalence in PFE ranged from 52-90% (16 studies, 487 patients; I² = 68%; Figure 6). Heterogeneity reflected differences in familial vs. sporadic cases and referral bias. Population-level prevalence remains unknown. Sixty-three variants identified. Domain 2 (Diagnostic Accuracy): "Failure to respond to orthodontic force" showed sensitivity 94% (95% CI: 91-97%) and specificity 96% (93-98%). "Progressive posterior open bite" showed sensitivity 92% (88-95%) and specificity 89% (84-92%). Reference standard heterogeneity (I² = 45-65%) addressed through bivariate and HSROC models. CBCT provided superior root resorption detection (97% vs. 68%; p < 0.001). Domain 3 (Canine Impaction): Open (91% [88-94%]) and closed (93% [89-95%]) exposure achieved comparable success (I² = 52%). Closed exposure was associated with shorter treatment duration (mean difference -4.7 months [-7.3 to -2.1]; I² = 64%; Figure 3) and lower postoperative pain (-1.9 VAS [-2.6 to -1.2]; I² = 58%; Figure 4). Prediction intervals (-9.8 to 0.4 months) support individualized technique selection. Funnel plots showed no significant publication bias (Figure 7). Domain 4 (Supernumerary): Spontaneous eruption after removal alone: 48-68% (I² = 71%; Figure 8); with adjunctive orthodontics: 81-90%. Heterogeneity reflected patient age, supernumerary morphology, and timing of intervention. Favorable factors: deciduous removal (OR 2.5-5.5), conical morphology (OR 3.0-6.5), incomplete root formation (OR 2.5-5.0). Domain 5 (PFE Management): Orthodontic force application failed in 88-98% and caused adjacent tooth ankylosis in 25-50%. Prosthodontic rehabilitation achieved functional occlusion in 82-94%. Implant success: 85-95%. Meta-analysis not performed due to critical heterogeneity. Domain 6 (Syndromic): Cleidocranial dysplasia alignment: 61-75%. Osteopetrosis extraction-associated osteomyelitis: 33%, favoring conservative management. Narrative synthesis only. Conclusions These findings support a paradigm shift toward genetically informed orthodontic decision-making across six integrated domains. PTH1R mutations are frequently reported in PFE, though population prevalence remains unknown. Open and closed canine exposure techniques have comparable success; closed exposure offers advantages in comfort and treatment duration. Early supernumerary intervention improves outcomes. Heterogeneity across domains reflects clinical diversity and was addressed through appropriate statistical methods. Orthodontic forces should be avoided in confirmed PFE. Registration Open Science Framework (DOI: 10.17605/OSF.IO/R5X76)